Closed total talar dislocation without fracture in a rare college athlete case. (October 2021) - Eda, Yusuke; Yanagisawa, Yohei; Matsumoto, Yukei; Mori, Toshio; Yamazaki, Masashi
Abstract: Total talar dislocation without a fracture is an extremely rare injury. It is often the result of high-energy trauma, such as that incurred after a fall, or owing to motor or vehicular accidents. Talar dislocations have poor outcomes owing to the frequent complications of infection, avascular necrosis and osteoarthritis attributed to open dislocations. We report herein a closed total talar dislocation without a fracture in a college athlete who was injured during sports activities. Specifically, a 20-year-old man was injured during a soccer game this led to a closed total talar dislocation. We performed closed reduction with image guidance subject to a popliteal sciatic nerve block, and placed a plaster cast below the knee. Radiographic studies after reduction revealed no associated fractures. After an eight week no-weight bearing period, we confirmed that there were no avascular necrosis signs on magnetic resonance images. Based on these findings, partial weight bearing was allowed. At 18 months post trauma, the athlete continues to play soccer despite the fact that he experiences a slight pain and limited range of motion. The blood supply to the talus is limited, and trauma, such as dislocation, can easily injure the blood supply, thus resulting in complications, such as avascular necrosis. The talus vascularity of the presented case was maintained by superior branches. We think that it is important to a) perform closed reduction early on, b) avoid any type of surgical operation that damages the limited talus blood supply, and c) allow weight bearing after the lack of avascular necrosis signs is confirmed. Although there is no standardized treatment, the talar dislocation treatment should be chosen to preserve the blood supply to the talus as much as possible.